Medicine, science and Merck - Vagelos, P. Roy (Cambridge University Press, 2004)
In Medicine, Science, and Merck, the authors trace the careers of a son of Greek immigrants as he mastered three professions and ultimately became the Chief Executive Officer of America's most admired corporation - the multinational, pharmaceutical giant, Merck & Co., Inc. As the authors show, there was hope even for a wise-cracking kid living through the hard times of the 1930s. Education brought out the scholar in Roy Vagelos, who left his family's small restaurant to attend the University of Pennsylvania, Columbia's Medical School, and Massachusetts General Hospital in Boston. At NIH, he mastered biochemistry; at Washington University he became a distinguished science administrator; and at Merck, he headed the pharmaceutical industry's most innovative laboratory and then became its CEO. Throughout, he never lost touch with his family values, his intense desire to help others, or his faith in the partnership principle and the competition that makes it work.
Includes index.
Keywords: Vagelos, P. Roy.; Merck Sharp & Dohme.; Vagelos, P. Roy; Merck Sharp & Dohme; Physicians -- United States -- Biography.; Medical scientists -- United States -- Biography.; Physician executives -- United States -- Biography.; Pharmaceutical industry.; Physician Executives; Drug Industry; United States; Médecins -- États-Unis -- Biographies.; Médecins cadres -- États-Unis -- Biographies.; Industrie pharmaceutique.; MEDICAL -- Physicians.; BIOGRAPHY & AUTOBIOGRAPHY -- Medical.; Pharmaceutical industry; Medical scientists; Physician executives; Physicians; Farmaceutische industrie.; Electronic book.; Personal Narrative; Autobiography; Biography; autobiographies (literary works); Personal narratives; Autobiographies; Biographies; Personal narratives.; Autobiographies.; Biographies.; Récits personnels.